Enhancing Antioxidant Potential of Lassi (A Traditional Indian Yoghurt based fermented milk drink) through fortification with Paneer (Indian Cottage Cheese) Whey partially fermented with Streptococcus thermophilus - Trisha Roy, Pinaki Ranjan Ray, Ankita Pandit, Surajit Mandal, Anindita Debnath; Subhadip Manik (Indian Journal of Dairy Science, 2026)
Lassi, a traditional Indian yoghurt-based fermented milk beverage, is known for its functional attributes, including antioxidant activity. The present study aimed to enhance the antioxidant potential of lassi by fortifying it with partially fermented paneer (Indian cottage cheese) whey. Paneer whey was fermented using Streptococcus thermophilus at 1.5% inoculum for 24 hours at 42 °C before being incorporated into the yoghurt base. Antioxidant activity of the fortified and control lassi samples was evaluated using ABTS [2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)] and DPPH (2,2-diphenyl-1-picrylhydrazyl) assays. The partially fermented whey fortified lassi exhibited significantly higher antioxidant activity (77.22 ± 0.50 µM TEAC in ABTS assay and 15.90 ± 0.08% DPPH inhibition) compared to the control (70.05 ± 0.67 µM TEAC and 12.41 ± 0.02%, respectively). These results demonstrate that fortifying lassi with partially fermented whey enhances its functional properties while also promoting sustainable utilization of whey, thereby reducing environmental burden and nutrient loss associated with paneer production.